Digital Media-Based Conflict Resolution Education Trends as Peace School Programs in Primary Schools - Wahyuningsih, Yona; Maftuh, Bunyamin; Sapriya, Sapriya; Darmawan, Deni (Universitas Pendidikan Indonesia, 2024)
This research aims to analyze the publication of Digital Media-Based Conflict Resolution Education Trends as a Peaceful School Program in Elementary Schools using VOSviewer with the Publish or Perish application. This research has been published for ten years (2018 to 2023), finding 996 articles relevant to the research. The results of this research found five areas pertinent to the study that were explored, namely the terms conflict resolution skills, digital media, programs, peacebuilding, and schools, with details of publications from 2013 to 2014 experiencing an increase. Publications from 2014 to 2015 had the same number of publications, namely 119, and increased in 2016. However, the number of articles from 2017 to 2022 continued to decline until only 15 articles were published. However, there will be an increase in 2023, reaching 29 articles. Data shows that the trend of digital media-based conflict resolution education as a peace school program in elementary schools is decreasing. Through VOSviewer, this research analyzes many published articles related to this topic. The impact of this review will be a reference for conducting further research on this topic in the future.